Plasmid profile and drug resistance pattern of zoonotic Salmonella isolates from Indian buffaloes - Singh, Bhoj Raj; Agarwal, Meenu; Chandra, Mudit; Verma, Meena; Sharma, Gautam; Verma, Jagdish Chandra; Singh, Vijay Pratap (The Journal of Infection in Developing Countries, 2010)
Background: Buffalo is the major source of animal protein in south-east Asia, including India; therefore, the presence of multiple drug resistance in Salmonella strains of buffalo meat and milk products is of immense public health concern. Methodology: Forty-six strains of Salmonella enterica subspecies enterica belonging to eight serovars (S. Anatum, 13; S. Weltevreden, 13; S. Rostock, 6; S. Typhimurium, 5; S. Gallinarum, 5; S. Stockholm, 1; S. Dublin, 1; and S. Orion, 2), isolated from buffalo meat and diseased buffaloes were studied for their antibiotic sensitivity and plasmid profile. Results: All except six strains of Salmonella had one or more plasmids. Virulence plasmid of ~35MdA was present in 39 isolates while 19 strains had one to six additional plasmids with molecular weight ranging from 1 Mda > 35 Mda. A plasmid-free S. Anatum strain was resistant to seven drugs including fluoroquinolones, while strains having six to seven plasmids were resistant to fewer antimicrobial drugs. One S. Anatum isolate, resistant to 11 antibiotics, had only one plasmid. Eight serovars of Salmonella could be divided into 28 resistotypes on the basis of antimicrobial sensitivity assay. Most strains were resistant to streptomycin (84.8%) followed by kanamycin (58.7%), gentamicin (52.2%), ampicillin (50%) and oxytetracycline (50%). Few strains were resistant to cefotaxime (2.2%), amoxycillin (2.2%) and newer fluoroquinolones (6.5%). Conclusion: Multiple drug resistance was common among Salmonella isolates of buffalo origin, particularly against aminoglycosides, oxytetracycin, ampicillin and cephalexin. Presence of plasmids is not mandatory for occurrence of multiple drug resistance in S. enterica strains.